53a-79=26a+29

Simple and best practice solution for 53a-79=26a+29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 53a-79=26a+29 equation:


Simplifying
53a + -79 = 26a + 29

Reorder the terms:
-79 + 53a = 26a + 29

Reorder the terms:
-79 + 53a = 29 + 26a

Solving
-79 + 53a = 29 + 26a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-26a' to each side of the equation.
-79 + 53a + -26a = 29 + 26a + -26a

Combine like terms: 53a + -26a = 27a
-79 + 27a = 29 + 26a + -26a

Combine like terms: 26a + -26a = 0
-79 + 27a = 29 + 0
-79 + 27a = 29

Add '79' to each side of the equation.
-79 + 79 + 27a = 29 + 79

Combine like terms: -79 + 79 = 0
0 + 27a = 29 + 79
27a = 29 + 79

Combine like terms: 29 + 79 = 108
27a = 108

Divide each side by '27'.
a = 4

Simplifying
a = 4

See similar equations:

| 106/4=x/12 | | =x^2+10x+9 | | 5x(-1)=10 | | X+1=5x-1 | | 53a-7.9=26a+29 | | 3/5(z-3)-11/5=-4 | | 7+2y=3.4 | | V/10.44-2.8=-4.422 | | X^2-9x^2+18=0 | | -5u+3(u+5)=29 | | Lnx^3/x^6 | | 14.63/9.315 | | 34z+63=-17z+471 | | 2/3(z-2)-11/3=-5 | | 5x+33=98 | | 10-10d=20 | | 2v=21 | | -80+-4x=120+6x | | (x+1)(x-1)=(x+1)(x-2) | | -80x+-4x=120+6x | | 3x-19=-70 | | 23-5=110 | | -(6y+1)-(-5y-8)=0 | | 3x^2-24x+28=0 | | 83overx=7 | | 3h-7=-7 | | -2(x-2)=-4x+14 | | -5-(-5/2) | | 33x-2+12x+2=180 | | -5/2-(-5/4) | | 33x-2+12+2=180 | | -75-11x=46 |

Equations solver categories